The Education of Health Counseling and Free Health Check-Up at GBI Rumah Persembahan - Elpriska Elpriska; Khairunnisa Situmorang; Dealita Khairani Daulay; Balqis Nurmauli Damanik; Asnita Yani; Nilawati Nilawati; Marta Imelda Br Sianturi (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service activity was carried out at GBI Rumah Persembahan, which aims to provide quality free medical services. This community service activity method uses lecture methods, demonstrations, question and answer methods and free treatment. This training involves students who are accompanied by accompanying lecturers from the Undergraduate Nursing Study Program, the Public Health Study Program, the Columbia Asia College of Health Sciences Undergraduate Program, and the Midwifery Study Program, the Columbia Asia College of Health Sciences Undergraduate Program, with community participants at GBI House of Persembahan. The results of the free health examination carried out on the community are the results of the evaluation of the free treatment provided by the training participants, which is generally in the good category with an average success of 90%.